Comparative Analysis of Cervical Cancer Screening Results in 2019 and 2020 in Shihezi Urban Areas, Xinjiang - Yu LIU, Yan WEI, Ping YANG (Zhongguo quanke yixue, 2022)
Background The results of cervical cancer containment have demonstrated regional differences in China, which may be due to various socioeconomic and cultural developments across regions. Understanding cervical cancer screening results in various regions is of a great significance for developing effective cervical cancer prevention strategies. Objective To perform a comparative analysis of the results of two yearly cervical cancer screening (2019 and 2020) in urban areas of Shihezi, Xinjiang, to estimate the changes in high-risk human papillomavirus (hrHPV) infection and cervical lesion detection rate in women. Methods A retrospective design was used. Participants were 46 994 women from Shihezi urban areas who underwent initial cervical cancer screening with an HPV test〔underwent once either between December 2018 and December 2019 (the 2019 yearly screening) or between January and June 2020 (the 2020 yearly screening) 〕 in Shihezi Maternal and Child Health Hospital, Shihezi People's Hospital, and First Affiliated Hospital, School of Medicine, Shihezi University during December 2018 to June 2020. Data of the screening results, including HPV infection rate and subtypes, Thinprep cytologic test results, and pathological diagnosis of cervical biopsy samples taken during a colposcopy were collected, and those of the 2019 yearly screening were compared with those of 2020 yearly screening. Results There were 18 378, and 28 616 attendees for 2019, and 2020 yearly screenings, respectively, and 44 746 of them finally completed the screening. The completion rate of cervical cancer screening in 2020 was higher than that in 2019 〔97.07% (27 779/28 616) vs (16 967/18 378) 〕 (P<0.05) . A total of 5 992 cases (12.75%) were detected with HPV infection, among them, the prevalence of HPV 16 and HPV 18 was 18.55% (1 112/5 992) , and that of other HPV subtypes was 81.45% (4 880/5 992) . The prevalence of HPV infections in participants of 2020 yearly screening〔11.09% (3 176/28 616) 〕was lower than that in participants of 2019 yearly screening〔15.32% (2 816/18 378) 〕 (P<0.05) . The prevalence of single-type HPV infections in participants of 2019 yearly screening was higher than that in participants of 2020 yearly screening 〔11.38% (2 092/18 378) vs 7.45% (2 674/28 616) 〕 (P<0.05) . The prevalence of multi-type HPV infections in participants of 2019 yearly screening was higher than that in participants of 2020 yearly screening〔3.94% (724/18 378) vs 1.75% (502/28 616) 〕 (P<0.05) . The prevalence of HPV was 10.37% (909/8 767) , 12.22% (1 916/15 677) , 13.71% (2 500/18 234) and 15.45% (667/4 316) , respectively, in four age groups of participants (30-39, 40-49, 50-59, and 60-65) in these two yearly screenings totally, showing an increase with age (P<0.05) . The prevalence of HPV showed a decrease in 30-39-year-old participants, so did it in 40-49-year-old, 50-59-year-old, and 60-65-year-old participants of 2020 yearly screening (P<0.05) . The top 5 prevalent single HPV subtypes found in 2019 yearly screening were HPV 52 (20.84%) , HPV 16 (14.48%) , HPV 53 (8.56%) , HPV 51 (7.93%) , and HPV 39/68 (7.60%) , while those found in 2020 yearly screening were HPV 52 (15.07%) , HPV 16 (12.64%) , HPV 58 (12.30%) , HPV 53 (10.25%) and HPV 66 (4.75%) . HPV 18 ranked as the 11th most prevalent single HPV subtype in both two screenings. The proportion of patients with pathological diagnosis of inflammation/condyloma and LSIL in cervical cancer screening in 2020 was lower than that in 2019 (P<0.05) . The 30-39-year-old participants of the 2020 yearly screening had lower prevalence of inflammation/condyloma detected by colposcopy than did those of the 2019 yearly screening (47.83% vs 74.36%) (P<0.05) . The 50-59-year-old participants of the 2020 yearly screening had lower prevalence of inflammation / condyloma detected by colposcopy than did those of the 2019 yearly screening (65.50% vs 77.22%) (P<0.05) . The 30-39-year-old participants of 2020 yearly screening had higher prevalence of colposcopy-detected low-grade squamous intraepithelial lesion (LSIL) than did those of 2019 yearly screening (31.30% vs 5.13%) (P<0.05) . The 40-49-year-old participants of 2020 yearly screening had higher prevalence of colposcopy-detected LSIL than did those of 2019 yearly screening (27.06% vs 16.07%) (P<0.05) . The 50-59-year-old participants of 2020 yearly screening had higher prevalence of colposcopy-detected LSIL than did those of 2019 yearly screening (23.64% vs 8.89%) (P<0.05) . Conclusion The completion rate of cervical cancer screening in 2020 was obviously better than that in 2019, but it still needs to be further improved. Compared with 2019, HPV infection rate decreased, the major prevalent HPV subtypes changed, and LISL prevalence increased in 30-39 and 50-59 age groups in 2020. Follow-up management is suggested to be strengthened in 30-39 and 50-59 age groups.